La comparaison en géographie. Contribution à partir de l’étude de la coopération intercommunale en France et au Brésil - Juliana Nunes Rodrigues (Confins)
This text discusses a set of issues concerning the processes of inter-municipal cooperation developing in France and in Brazil. On the one hand, it brings back some conclusions explored during the realization of surveys made in the region of Rhône-Alpes, in France, and in the state of Rio de Janeiro, Brazil. On the other hand, it examines the influence of the organization of the French and Brazilian States in order to comprehend the particularities of cooperative practices between municipalities in both countries. The objective is to valorise the comparative method, thus expanding the debate about the strengthening of local management structures and the different possibilities of inter-municipal cooperation within two very distinct State models.